2024
DOI: 10.1186/s40942-024-00525-9
|View full text |Cite
|
Sign up to set email alerts
|

Review of real-world evidence of dual inhibition of VEGF-A and ANG-2 with faricimab in NAMD and DME

Fernando M Penha,
Maliha Masud,
Zoha A. Khanani
et al.

Abstract: Management of vitreoretinal disorders (e.g., neovascular age-related macular degeneration [nAMD] and diabetic macular edema [DME]) have assumed the standard therapy of lifelong anti-VEGF injections with drugs like aflibercept, brolucizumab, ranibizumab and bevacizumab. However, the burden imposed on patients is a major deterrent for continual therapy and recovery. Faricimab, a bispecific antibody, blocking both VEGF-A and Ang-2 molecules, produces a comparable functional and anatomical results, with less injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The FARWIDE-AMD and the FARETINA-AMD studies found that visual acuity remained stable after three injections in previously treated patients with anti-VEGF and showed improvement in naïve patients. 84 85 This is also consistent with the reported improvement after three injections of clinical outcomes in the TRUKEE study, where the improvements were mainly in the previously untreated patients, with gains of 8.1 letters in BCVA and reductions in the retinal thickness of −80.1 µm. 86 Currently, real-world studies support our results on maintaining functional visual acuity outcomes and improving anatomical outcomes with the use of faricimab.…”
Section: Discussionsupporting
confidence: 88%
“…The FARWIDE-AMD and the FARETINA-AMD studies found that visual acuity remained stable after three injections in previously treated patients with anti-VEGF and showed improvement in naïve patients. 84 85 This is also consistent with the reported improvement after three injections of clinical outcomes in the TRUKEE study, where the improvements were mainly in the previously untreated patients, with gains of 8.1 letters in BCVA and reductions in the retinal thickness of −80.1 µm. 86 Currently, real-world studies support our results on maintaining functional visual acuity outcomes and improving anatomical outcomes with the use of faricimab.…”
Section: Discussionsupporting
confidence: 88%
“…The safety profile of faricimab has been demonstrated to be favourable, with rates of inflammation and endophthalmitis comparable to those observed in other widely used treatments 25 .…”
Section: Faricimabmentioning
confidence: 79%